2008
DOI: 10.1136/jech.2007.065391
|View full text |Cite
|
Sign up to set email alerts
|

Suicide methods in Europe: a gender-specific analysis of countries participating in the "European Alliance Against Depression"

Abstract: Objective:To identify the most frequent gender-specific suicide methods in Europe.Design:Proportions of seven predominant suicide methods utilised in 16 countries participating in the European Alliance Against Depression (EAAD) were reported in total and cross-nationally. Relative risk (RR) relating to suicide methods and gender was calculated. To group countries by pattern of suicide methods, hierarchical clustering was applied.Setting and participants:Data on suicide methods for 119 122 male and 41 338 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
166
3
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(210 citation statements)
references
References 36 publications
14
166
3
14
Order By: Relevance
“…However, when controlling for all the other variables, male sex was no longer a risk factor for suicide attempts by the elderly. This may be due to the different rates of suicide methods between our study, characterized by more frequent low lethality drug overdose, and other studies, characterized by more frequent highly lethal methods of suicide, such as hanging and shooting [34][35][36] . It is also reflected in our finding that highly lethal drug overdose was identified as a risk factor for suicide attempt among the elderly.…”
Section: Discussioncontrasting
confidence: 40%
“…However, when controlling for all the other variables, male sex was no longer a risk factor for suicide attempts by the elderly. This may be due to the different rates of suicide methods between our study, characterized by more frequent low lethality drug overdose, and other studies, characterized by more frequent highly lethal methods of suicide, such as hanging and shooting [34][35][36] . It is also reflected in our finding that highly lethal drug overdose was identified as a risk factor for suicide attempt among the elderly.…”
Section: Discussioncontrasting
confidence: 40%
“…The choice of method of suicide varies with gender, culture and availability of method, although the reasons are poorly understood, and both the intended level of lethality and risk of damaging the body appearance have been suggested to explain the reduced likelihood of use of violent methods by women. [25] The reduced risk of suicide by firearms and explosives in veteran men in our study compared with non-veterans contrasts with serving personnel, where 20% of suicides in men result from this cause although the rate has reduced from a peak of 6 per 100,000 per year in the army in the mid-1990s to around 1 per 100,000 per year in 2012. [26] Our results differ from a US study which showed an increased risk of firearm-related suicide in both male and female veterans compared with the wider population.…”
Section: After Data Cleansing To Remove Incomplete or Invalid Recordsmentioning
confidence: 98%
“…Such research tends to suggest that males are more likely than females to use firearms in committing suicide. 4,16,[19][20][21][22] In this study the proportion of males in the FAS group was 4.54 times the proportion in the n-FAS group. This is traditionally rationalised as reflecting the fact that males are more likely to own a firearm than females and that males tend to use more violent and lethal methods.…”
Section: Betweenmentioning
confidence: 99%
“…Being male is perhaps the greatest risk factor, accounting for the majority of suicides across Europe. 4 Research would also tend to suggest that males make up a greater proportion of firearms suicides than other suicides, 4 in part explained by the reality that males are more likely to own, and have access to, a firearm than are females. 5,6 There have been mixed findings on the relationship between age and firearms suicide.…”
Section: Introductionmentioning
confidence: 99%